Gastric Tuberculosis Mimicking Cancer Manifestations in Peru - Fernando Barreda; Nadia Malpartida-Beraún; Claudia Barreda; Melvy Guerrero (Clinical and Research Journal in Internal Medicine, 2023)
Tuberculosis is a high-incidence public health problem in Peru. In our context, Tuberculosis is seen commonly as a pulmonary infection. Extrapulmonary tuberculosis as gastric is rare, both as a primary or secondary infection, with just a few case reports published about these kinds of presentations. This case report presents a 44-year-old female patient with weight loss, dyspepsia, and abdominal pain. Upper endoscopy reveals antral polypoid masses and a gastric ulcer. Abdominal CT shows lymph nodes and stomach wall thickening. Biopsies results were negative for malignancy and positive for granulomas. Sputum acid-fast bacilli smear on microscopic examination was positive. Coexistent pulmonary, gastric tuberculosis, and human immunodeficiency virus infection mimicking gastric cancer were confirmed. We will present this case in detail below.